BETWEEN IMAGINING AND REMEMBERING AN EXTENSION TO THE GOTHENBURG MUSEUM OF ART - Johansson, Per (My University, 2023)
Gothenburg Museum of Art is set to be extended and remodelled, with an architectural competition being held in 2023 to determine the design for the project. This thesis aims to offer a deeper reflection on the competition, and potentially explore broader questions beyond what the competition alone may address. The site at Götaplatsen houses some of the most prominent cultural institutions in the city and it presents a fascinating history as the entrance to the Gothenburg exhibition in 1923. Since its inauguration the museum has been altered and extended two times, in 1968 and 1996. During the years there has also been several proposals for how to extend the museum and modify Götaplatsen. The thesis explores these layers, the built, the planned, the unrealized, the alternate proposals, the modified etc. The main focus of the thesis explores how one as a designer should relate to the multiplicity of references which the postmodern condition consists of. When adding or modifying buildings in an urban context questions of what should be preserved or restored and what parts of the story should be told or re-imagined emerge. The secondary focus of the thesis deals with how certain core conflicts of the museum institution can be resolved, such as that of protecting artworks and at the same time making them available, or that of simultaneously allowing for freedom of movement as well as spaces for contemplation. The process of designing began by investigating the historical layers and the related discussions surrounding the site, by for example examining drawings at the regional archive. After this initial phase the design task later evolved into how both qualities from the original ideas behind the building (from ARES winning competition entry in 1918) as well as later proposals (in particular professor Lars Ågrens extension proposal) could be combined into a coherent new design proposal and in a sense "finishing" what was started. This proposed design also meets and adapts to the buildings current state and present-day requirements of the museum institution.
Keywords: Gothenburg Museum of Art, addition, cultural heritage